‘Georgian Film Is a Completely Unique Phenomenon.’ A Film Scene with History, or Georgian Cinema in the Emancipation Loop - Buder Bernd (Comparative Southeast European Studies, 2018)
With a view of Georgian cinema under the current spotlights of various international film festivals, the author reviews the state of the art of Georgian film production, linking it to the impressively long history of Georgia’s cinematographic production. Recently, a targeted film promotion policy has focused on international co-productions and on fostering cooperative ventures with European partners. Among the young filmmakers a remarkably large proportion are female.